2018
DOI: 10.3389/fmicb.2018.00644
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Shunting, Polycistronic Translation, and Evasion of Antiviral Defenses in Plant Pararetroviruses and Beyond

Abstract: Viruses have compact genomes and usually translate more than one protein from polycistronic RNAs using leaky scanning, frameshifting, stop codon suppression or reinitiation mechanisms. Viral (pre-)genomic RNAs often contain long 5′-leader sequences with short upstream open reading frames (uORFs) and secondary structure elements, which control both translation initiation and replication. In plants, viral RNA and DNA are targeted by RNA interference (RNAi) generating small RNAs that silence viral gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 146 publications
(286 reference statements)
0
39
0
Order By: Relevance
“…Antiviral defense restricts viral RNA translation, virus replication, movement, or virion assembly, resulting in reduced virus accumulation and/or a delay in virus movement with or without a hypersensitive response [ 26 , 27 , 28 ]. Antiviral defense mechanisms are reviewed in [ 26 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral defense restricts viral RNA translation, virus replication, movement, or virion assembly, resulting in reduced virus accumulation and/or a delay in virus movement with or without a hypersensitive response [ 26 , 27 , 28 ]. Antiviral defense mechanisms are reviewed in [ 26 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of reinitiation is not fully understood in any organism (Gunisova, Hronova, Mohammad, Hinnebusch, & Valasek, 2018), but it is clear that spontaneous reinitiation is common only after short ORFs, typically uORFs in the 5' leader (von Arnim et al, 2014). In the exceptional case of cauliflower mosaic virus (CaMV), reinitiation after long coding sequences is boosted by the viral transactivator protein, TAV, a scaffold that coordinates with initiation factors such as eIF3 and eIF4B, other host proteins, and the ribosome (Pooggin & Ryabova, 2018). Extensive work on the 5' leader of CaMV and related pararetroviruses has suggested that the reinitiating 40S has different properties from a cap-dependent 40S.…”
Section: Translation Reinitiationmentioning
confidence: 99%
“…Extensive work on the 5' leader of CaMV and related pararetroviruses has suggested that the reinitiating 40S has different properties from a cap-dependent 40S. For example, even in the absence of TAV, the reinitiating 40S is capable of "shunting" past a 500 nt secondary structure in the CaMV 5' leader ( Figure 3b), and its ability to distinguish authentic from near-cognate start codons may be reduced (Pooggin & Ryabova, 2018).…”
Section: Translation Reinitiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, the 5'-proximal sORF within the leader is translated prior to encountering the hairpin structure, which then forces the ribosome to shunt to a downstream portion of the mRNA sequence (pairing ribosome shunting and reinitiation, which is mentioned below). While identified in plant viruses, ribosomal shunting also occurs in animal viruses and in cellular mRNAs (Pooggin and Ryabova, 2018).…”
Section: Ribosome Shuntingmentioning
confidence: 99%